Essential fatty acids in full term infants fed breast milk or formula. Issue 1 (January 1995) - Decsi, T.; Thiel, I.; Koletzko, B.
Abstract : To determine the biochemical effects of the fatty acid composition of plasma lipids, two groups of 10 healthy full term infants who were either exclusively breast fed or received a formula with similar contents of linoleic and alpha linolenic acids, but without long chain polyunsaturated (LCP) fatty acids, were studied prospectively. Plasma phospholipid, triglyceride, and sterol ester fatty acids were determined at the age of 2, 4, and 8 weeks by high resolution capillary gas chromatography. Breast fed infants maintained stable LCP fatty acid concentrations throughout the study. Formula fed infants had significantly lower median values of arachidonic acid (AA) at the ages of 2 (6.9 v 9.5% wt/wt) and 4 weeks (5.9 v 7.9%) and docosahexaenoic acid (DHA) at the ages of 4 (1.1 v 1.7%) and 8 weeks (1.0 v 1.7%) in plasma phospholipids. Median AA values in triglycerides were also significantly lower in the infants receiving formula at the ages of 2 (0.4 v 0.6%) and 4 weeks (0.3 v 0.6%). It is concluded that formula fed full term infants are unable to match the omega-3 and omega-6 LCP status of breast fed full term infants until at least two months after birth.